1999
DOI: 10.1074/jbc.274.13.8624
|View full text |Cite
|
Sign up to set email alerts
|

Cripto-1 Indirectly Stimulates the Tyrosine Phosphorylation oferb B-4 through a Novel Receptor

Abstract: Cripto-1 (CR-1) is a recently discovered protein of the epidermal growth factor family that fails to directly bind to any of the four known erb B type 1 receptor tyrosine kinases. The present study demonstrates that CR-1 indirectly induces tyrosine phosphorylation of erb B-4 but not of the epidermal growth factor-related receptors erb B-2 and erb B-3 in different mouse and human mammary epithelial cell lines. In addition, downregulation of erb B-4 in NMuMG mouse mammary epithelial cells and in T47D human breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 34 publications
(39 reference statements)
1
46
0
Order By: Relevance
“…In addition, Cripto-1 is frequently coexpressed with other EGF-related peptides, such as TGFα, amphiregulin (AR), and heregulin in human primary breast carcinomas suggesting that Cripto-1 might cooperate with these different growth factors in supporting the autonomous proliferation of breast cancer cells. A positive correlation between nuclear HER-4 expression and Cripto-1 expression in primary human breast carcinomas has also been described [96] further supporting the finding that Cripto-1 can indirectly enhance the tyrosine phosphorylation of HER-4 [97].…”
Section: Diagnostic and Therapeutic Applicationsupporting
confidence: 64%
“…In addition, Cripto-1 is frequently coexpressed with other EGF-related peptides, such as TGFα, amphiregulin (AR), and heregulin in human primary breast carcinomas suggesting that Cripto-1 might cooperate with these different growth factors in supporting the autonomous proliferation of breast cancer cells. A positive correlation between nuclear HER-4 expression and Cripto-1 expression in primary human breast carcinomas has also been described [96] further supporting the finding that Cripto-1 can indirectly enhance the tyrosine phosphorylation of HER-4 [97].…”
Section: Diagnostic and Therapeutic Applicationsupporting
confidence: 64%
“…Non-NRG ligands must also be considered. ErbB4 in tumor cells or heterologous system can be activated by other members of the EGF family (Beerli and Hynes, 1996;Bianco et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using the refolded CRIPTO peptide have shown that CRIPTO can induce tyrosine phosphrylation of the SH2 adapter protein She in HC-11 cells, resulting in increased association of She with Grb2 and elevated MAPK kinase activity [2,9]. More recently it has been shown that recombinant CRIPTO can transactivate erbB-A receptor, but not EGF receptor, erbB-2 and erbB-3 [10]. These results suggest that Cripto may be involved in a Ras signaling pathway.…”
Section: Introduction 51 Background and Significancementioning
confidence: 84%